A critical assessment on synergistic improvement in PCM based thermal batteries. (January 2021) - Naghavi, M.S.; Metselaar, H.S.C.; Ang, B.C.; Zamiri, G.; Esmailzadeh, A.; Nasiri-Tabrizi, B.
Abstract: Current solar water heaters still facing some weaknesses in the performance and efficiency loss, such as the dependency of heat transfer rate between the heat pipe and the cold water to temperature difference and flowrate, and stratification effect in the hot water tank, which all affects total deliverable hot water volume to the end-user. Within the past decade, many research activities attacked these issues and provided different types of solutions. One of the solutions is using phase change materials as a thermal energy storage unit or as part of it. This paper compares 21 parameters related to the technical specifications, structural design, economic, and health related issues of four of the full-scale experimental studies of solar water heaters with latent heat thermal energy storage. This study is essential and indicative to facilitate and pave the way for future research and development of such products. All of the reported solar water heater systems with latent heat thermal energy storage unit systems were the primary design, with no optimization study. With the positive improvement in the performance of these units, it could be expected that the new generation of SWH systems will utilize the advantages of the latent heat storage unit, by using PCMs. There is potential for improvement in these systems in the fields related to the optimization of the TES unit, infrastructure, and cost of the system. The impact of weather conditions in different climatic conditions needs more investigation. Highlights: Four designs of solar water heater with TES unit were selected and compared. TES unit utilizes latent heat storage of PCMs. The report compares performance, structural, economic and health related issues. The report facilitates and paves the way for future research and development.